2020
DOI: 10.1186/s13019-020-01305-w
|View full text |Cite
|
Sign up to set email alerts
|

Video-Assisted Thoracoscopic Surgery vs Thoracotomy for Non-Small Cell Lung Cancer Greater Than 5 cm: Is VATS a feasible approach for large tumors?

Abstract: Background VATS lobectomy is a recommended surgical approach for patients with early-stage lung cancer. However, it is still controversial in locally advance disease. This study was conducted to compare intraoperative and postoperative results of VATS and thoracotomy in patients with tumors greater than 5 cm. Methods From January 2014 to December 2018, 849 patients underwent lobectomy or pneumonectomy for the treatment of non-small-cell lung cancer at our center. The inclusion criterion of this study was pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 19 publications
1
17
0
Order By: Relevance
“…A retrospective study of stage IA NSCLC patients who underwent lobectomy demonstrated that VATS was associated with increased 5-year OS compared to open thoracotomy (100% vs. 87%, p = 0.01) and DFS (100% vs. 86%, p = 0.03) ( 63 ). In tumors greater than 5 cm, VATS was associated with greater OS and DFS ( p = 0.056 and 0.031, respectively) compared to open thoracotomy ( 64 ), and in clinical N2 lung cancer, VATS showed similar 5-year OS (50.5% vs. 48.4%, p = 0.127) and DFS (60.5% vs. 44.6%, p = 0.069) ( 65 ). A study of oncological outcomes in patients who underwent surgical resection for early-stage lung cancer found no differences in 5-year OS (71.6% vs. 65.9%, p = 0.36) and DFS (75.2% vs. 69.2%, p = 0.55) between VATS and open lobectomy ( 66 ).…”
Section: Perioperative Modulation Of Inflammatory Response and Oncolo...mentioning
confidence: 99%
“…A retrospective study of stage IA NSCLC patients who underwent lobectomy demonstrated that VATS was associated with increased 5-year OS compared to open thoracotomy (100% vs. 87%, p = 0.01) and DFS (100% vs. 86%, p = 0.03) ( 63 ). In tumors greater than 5 cm, VATS was associated with greater OS and DFS ( p = 0.056 and 0.031, respectively) compared to open thoracotomy ( 64 ), and in clinical N2 lung cancer, VATS showed similar 5-year OS (50.5% vs. 48.4%, p = 0.127) and DFS (60.5% vs. 44.6%, p = 0.069) ( 65 ). A study of oncological outcomes in patients who underwent surgical resection for early-stage lung cancer found no differences in 5-year OS (71.6% vs. 65.9%, p = 0.36) and DFS (75.2% vs. 69.2%, p = 0.55) between VATS and open lobectomy ( 66 ).…”
Section: Perioperative Modulation Of Inflammatory Response and Oncolo...mentioning
confidence: 99%
“…Non-intubated thoracic surgical procedures are widely used to perform minor and major thoracic surgeries, and is a feasible technique to perform pleural and lung biopsies, metastasectomies, anatomical lung resections and surgeries to pneumothorax (66,67). The main principle is to create iatrogenic pneumothorax, thus, the operator has enough space to implement the surgery and to avoid the use of double-lumen endotracheal tube.…”
Section: The Immune and Oncological Effects Of Nonintubated Thoracic ...mentioning
confidence: 99%
“…In a study, we conducted in our clinic, which included 60 patients with tumors larger than 5 cm, mean drainage time and postoperative length of hospital stay were significantly shorter [50] (Figure 6).…”
Section: The Role Of Vats In the Surgical Treatment Of The Lung Cancermentioning
confidence: 99%
“…Moreover, many studies have demonstrated that VATS can be applied with low complication rates after neoadjuvant therapy or in cases with large tumors [49][50][51][52].…”
Section: Contraindications For Vats Anatomic Lung Resectionmentioning
confidence: 99%